2010
DOI: 10.1377/hlthaff.2010.0038
|View full text |Cite
|
Sign up to set email alerts
|

Medical-Legal Partnerships: Transforming Primary Care By Addressing The Legal Needs Of Vulnerable Populations

Abstract: Health care is undermined when patients don't receive the benefit of laws intended to address social determinants of health, such as housing and food. Medical-legal partnerships, which now exist in more than 200 clinical sites in the United States, integrate lawyers into health care to address legal problems that create and perpetuate poor health. This paper describes how such medical-legal partnerships can change clinical systems-for example, by adding legal form letters to electronic health records to help l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 9 publications
0
99
0
2
Order By: Relevance
“…Doctors must learn from lawyers to screen patients for unmet social and economic needs in areas such as income, housing and utilities, education, immigration, and personal and family stability; they must also refer patients with unmet needs to lawyers. Lawyers must learn from doctors how to resolve issues during phone consults, advise doctors about other legal and social services, and schedule patients for intakes and treatment at their legal clinic.Research shows that MLP reform allows patients to leave medical clinics with comprehensive prescriptions for improved health (Sandel et al 2010). For instance, asthmatic patients not only obtain prescriptions for inhalers, but also strategies to compel recalcitrant landlords to remove mold and exterminate pests (Zuckerman et al 2004).…”
mentioning
confidence: 99%
“…Doctors must learn from lawyers to screen patients for unmet social and economic needs in areas such as income, housing and utilities, education, immigration, and personal and family stability; they must also refer patients with unmet needs to lawyers. Lawyers must learn from doctors how to resolve issues during phone consults, advise doctors about other legal and social services, and schedule patients for intakes and treatment at their legal clinic.Research shows that MLP reform allows patients to leave medical clinics with comprehensive prescriptions for improved health (Sandel et al 2010). For instance, asthmatic patients not only obtain prescriptions for inhalers, but also strategies to compel recalcitrant landlords to remove mold and exterminate pests (Zuckerman et al 2004).…”
mentioning
confidence: 99%
“…[72][73][74] The MLP model was designed to meet these SDH, and MLPs currently exist in ∼300 hospitals and health centers nationally. 75 MLPs generally share 3 objectives: (1) to provide direct civil legal services to families who have a civil legal need that affects health; (2) to transform both health and legal organizations; and (3) to provide systemic advocacy to improve laws and policies affecting health outcomes.…”
Section: Mlpsmentioning
confidence: 99%
“…75 MLPs generally share 3 objectives: (1) to provide direct civil legal services to families who have a civil legal need that affects health; (2) to transform both health and legal organizations; and (3) to provide systemic advocacy to improve laws and policies affecting health outcomes. [72][73][74][75][76][77] The National Center for Medical-Legal Partnership provides support for new and existing programs, helps to build the evidence base for MLPs, encourages interdisciplinary education, and focuses the health dialogue on at-risk populations. 75 Studies indicate that MLPs can reduce subjective stress and improve self-reported well-being, legal problem-solving skills and sense of empowerment, and health care utilization and self-reported health and well-being.…”
Section: Mlpsmentioning
confidence: 99%
See 1 more Smart Citation
“…88,92,93 Medical-legal partnerships link legal services with primary care to identify and intervene when families require legal services for poverty or social environment concerns, such as housing or food insecurity. [94][95][96] The Reach Out and Read program has become a basic staple of WCC; this modest intervention improves the home learning environment for children by promoting early literacy habits, particularly for children who might otherwise not have an optimal home learning environment. [97][98][99] Proven comprehensive models, however, remain elusive.…”
Section: Community Connections Approachmentioning
confidence: 99%